(untitled) (The Pretoria Student Law Review, 2021)
To determine, for the purposes of the Value-added Tax Act (‘VAT Act’)1 whether a supply consists of a composite supply or several distinct supplies is paramount. Amongst other reasons, it impacts on how the entire supply should be treated under the VAT Act (i.e. standard, exempt or zero-rated). The treatment of the supply not only affects the applicable tax rate, but it also impacts the value added tax (‘VAT’) claimable or payable when acquiring or selling the supplies. The incorrect treatment of the supply puts the taxpayer at risk since the tax authority may raise reassessments and impose penalties. Therefore, where a supply entails the supply of goods or services or both, it is essential for a vendor to correctly treat the transaction to avoid these repercussions. The aim of this paper is to illustrate that the South African (SA) approach to determining whether a separate part is made is not in line with the international approach. The domestic approach appears to ignore essential elements that are widely accepted when deciding if a supply is single or composite. This paper argues that this approach may in some cases yield unfavourable results in term of VAT. The paper is structured as follows; Part I, briefly discusses the meaning of the composite supply; Part II, provides the South African approach to composite supply; Part III, outlines how the EU and CAN jurisdiction’s VAT systems treat the composite supply; Part IV, points out the shortcomings of the South African approach to the treatment of the composite supply; Part V, outlines the recommendations may be implemented so to align the South African approach with the international perspective.